Educational technology on COVID-19 for families of children and adolescents with sickle cell disease - Patrícia Peres de Oliveira; Elaine Cristina Rodrigues Gesteira; Rhillary Lorraine de Souza; Nayara Cristine Protte de Paula; Letícia Camilo Santos; Walquíria Jesusmara dos Santos; Edilene Aparecida Araújo da Silveira
ABSTRACT Objective: to construct and validate educational technology on COVID-19 and essential care for families of children/adolescents with sickle cell disease. Methods: this is a methodological study, in three stages: 1) elaborated educational technology, using the Doak, Doak and Root theoretical-methodological model; 2) content and appearance validation by the content validity coefficient. Delphi technique was applied in two rounds (Delphi I [12 judges]/Delphi II [11 judges]); 3) conducting a pilot test with six families. Results: "Sickle cell disease and COVID-19: essential care" included: consequences of COVID-19 in sickle cell disease, guidelines for reducing the risks of contracting the virus and having complications, signs and symptoms of COVID-19, guidelines in case of child/adolescent with suspicion or symptoms of COVID-19. Global content validity coefficient (Delphi II): 0.98. Conclusion: educational technology presented content and appearance validity for families of children/adolescents with sickle cell disease, related to COVID-19.